Changing misconceptions about sexual harassment in a sample of Lithuanian students - Čeponytė, Monika; Žardeckaitė-Matulaitienė, Kristina (Psichologija, 2018)
Sexual harassment is one of the most common gender-based discrimination forms in Lithuania and is experienced at least once in a lifetime by 35% of women from the age of 15. The recently published results of a survey implemented by the Lithuanian Students’ Union (2018) showed that 5 percent of students from different universities and colleges in Lithuania possess experiences that they identify as sexual harassment; however, the majority of them are afraid to report these incidents because of the negative public reaction or because of the potential impact on their academic achievements. An absence of a clear definition and the prevailing misconceptions about sexual harassment, as well as a lack of information about the procedure of reporting sexual harassment, makes sexual harassment an ambiguous problem that became the topic of public discussion but has not been dealt with properly. Various studies show promising results of different sexual harassment prevention activities and makes it possible to assume that such training might be a way of reducing the prevalence of sexual harassment in the academic environment. The aim of this study was to assess the effectiveness of a brief sexual harassment training course in reducing positive attitudes toward sexual harassment and the acceptance of sexual harassment myths, as well as improving the identification of sexual harassment situations, in a sample of Lithuanian students.Thirty-two students (28 females and 4 males) took part in this research and attended a brief sexual harassment training that lasted for 1 hour 30 minutes. The participants’ age varied from 19 to 28 years, the average age being 22.9 years (SD = 2.19). A self-reported questionnaire consisted of several scales: the Sexual Harassment Attitude Scale (Cronbach α – 0,86) (Mazer & Percival, 1989) measuring the participants’ positive attitudes toward sexual harassment; the Illinois Sexual Harassment Myth Acceptance Scale (Cronbach α – 0,92) (Lonsway, Cortina, & Magley, 2008); 8 self-report scenarios were created based on Bursik (1992) and consultations with the Office of the Equal Opportunities Ombudsperson to measure the participants’ perceptions of sexual harassment. Additional demographic questions were also included.The results revealed significant changes in sexual harassment perception, myth acceptance and attitudes toward sexual harassment before and after the training. Study results showed significantly reduced positive attitudes toward sexual harassment and that the participants were less likely to attribute sexual harassment to being a part of a romantic relationship. Even though the results showed a significantly lower “Normal heterosexuality” subscale in terms of the results on the Sexual Harassment Myth Acceptance Scale, participants were, however, more likely to attribute blame to the victim of sexual harassment after the prevention training. The study results also revealed that after the training, the participants evaluated more sexual harassment scenarios as sexual harassment than before the training.
Keywords: sexual harassment; sexual harassment myths; sexism; sexist beliefs